Sanitasi Pribadi Anak: Kebersihan Handuk Sebagai Upaya Pencegahan Penyakit Kulit - Salma Sakinah; Sakha Andini; Nur Hasna Jauza; Yani Achdiani (CV. ITTC INDONESIA, 2025)
Personal hygiene is one of the most important measures in maintaining health, especially in preventing skin diseases. One aspect of personal hygiene that is often overlooked is towel hygiene. Towels that are used repeatedly without being washed properly can become a breeding ground for bacteria, fungi, and other microorganisms that can cause various skin problems such as itching, irritation, fungal infections, and dermatitis. This article aims to examine the role of towel hygiene as a measure to prevent skin diseases based on a review of various health and environmental journals in Indonesia. The results of the study show that sharing towels, rarely washing towels, and not drying towels properly can increase the risk of skin disease transmission. Therefore, habits of maintaining towel hygiene, such as washing towels regularly, drying them thoroughly, and not sharing towels, are simple yet effective steps in supporting personal sanitation and preventing skin diseases. These efforts are expected to raise public awareness of the importance of clean and healthy living behaviors in daily life.